New contribution to the peritrichous genus Ophrydium (Protista, Ciliophora) with notes on the morphology, taxonomy, and phylogeny of a well‐known species Ophrydium crassicaule Penard, 1922. (15th March 2022) - Wu, Tong; Wang, Zhe; Lu, Borong; Lei, Jingtao; Al‐Rasheid, Khaled A.S.; Sheng, Yalan
Abstract: The peritrichous genus Ophrydium is relatively distinctive since its colonies have a gelatinous lorica. In the present work, one morphologically well‐described species, Ophrydium crassicaule, was collected from a freshwater habitat in China. Both morphological characters and sequence data for SSU rDNA, ITS1‐5.8S‐ITS2 region and LSU rDNA were obtained. Morphologically, O .  crassicaule is characterized by its elongated vase‐shaped zooid, single‐layered peristomial lip, dichotomously branched stalk, colony with gelatinous lorica, and infundibular polykinety 3 (P3) containing one short inner row and two long outer rows. Phylogenetic analyses revealed that the genus Ophrydium is monophyletic and nests within the family Vorticellidae. In addition, we briefly revise the nominal congeners for aiding the species identification in future studies.